Business in practice - Rui, Sisi (2022)
Business in practice is a three-week intense working experience. It’s required to accomplish a simulation of managing an automobile manufacturer company within a team with diverse functions and diverse cultural background. It was inspiring and motivational. This report demonstrates my personal reflections during this journey as well as the simulation firm analysis.